THE ROLE OF RESTAURANT TAXES IN INCREASING REGIONAL REVENUE IN SLEMAN - Meiba Ayumy Subroto; Sava Lidya Utami; Kristina Ineke Asa; Wicaksono, Galih; Adit Ardiansyah (Journal of International Multidisciplinary Research, 2024)
Regional Autonomy is a strategic step taken by the government to overcome uneven development in Indonesia where local governments are responsible for improving regional development. One of the important factors for the success of regional development is the effectiveness of local revenue reflected through local taxes. The effectiveness of local taxes is a study of the collection performance carried out by the Regional Revenue Service during one fiscal year to determine the effectiveness of local taxes realized with the set target. Sleman Regency is one of the regions that currently has high Regional Original Revenue and one of the sources of revenue is restaurant tax. Sleman as one of the strategic areas provides many opportunities to increase Regional Original Revenue through taxes, including restaurant tax. The results of calculations and observations of data on the effectiveness of restaurant tax revenue in Sleman Regency for the last 4 years starting from 2019 to 2022 have fluctuated. The average effectiveness rate that reaches 112% indicates a very effective achievement. In terms of restaurant tax contribution to Regional Original Revenue, 2022 is the year with the largest restaurant tax contribution over the past 4 years because in that year Indonesia has begun to recover from covid-19, but the contribution of restaurant tax to Sleman Regency's Original Revenue is still in the category of less with an average restaurant tax contribution of 10.66%.